PTPN2 Inhibition Disrupts Mitochondrial Renewal and Blocks TFRC‐Mediated Mitophagy to Exert Anti‐Tumor Activities in ALK‐Positive Anaplastic Large Cell Lymphoma - Wei‐Ting Wang; Zi‐Wen Duan; Tong‐Yao Xing; Wei Hua; Kai‐Xing Du; Chun‐Yu Shang; Yi‐Fan Wu; Li Wang; Jian‐Yong Li; Rui Gao; Jin‐Hua Liang; Wei Xu (Advanced Science)
Abstract Anaplastic large cell lymphoma (ALCL) is a heterogeneous subtype of T‐cell lymphoma usually driven by genetic alterations affecting the anaplastic lymphoma kinase (ALK) gene. Despite the relatively favorable prognosis of ALK‐positive (ALK+) ALCL, approximately 30–40% of patients experience relapses or disease progression. This work identifies protein tyrosine phosphatase PTPN2 as a critical gene essential for the growth and survival of ALK+ ALCL by CRISPR/Cas9 editing. PTPN2 depletion can significantly suppress tumor cell proliferation, induce apoptosis, and provoke cell cycle arrest. Mechanistically, PTPN2 negatively regulates transferrin receptor (TFRC) expression to promote mitochondrial renewal via PTEN induced kinase 1 (PINK1)‐PRKN (parkin RBR E3 ubiquitin protein ligase)‐mediated mitophagy. The process functions independently of ferroptosis. Interestingly, TFRC is directly regulated by the transcription factor hypoxia‐inducible factor 1 alpha (HIF1A) in its promoter. Notably, an orally bioavailable potent PTPN2/N1 active‐site inhibitor ABBV‐CLS‐484 (AC484) demonstrates significant therapeutic potential against ALK+ ALCL by disturbing mitochondrial renewal and blocking TFRC‐mediated PINK1‐PRKN‐dependent mitophagy to exert anti‐tumor activities, providing critical insights into the selection of targeted treatment strategies for ALK+ ALCL patients and a strong rationale for advancing AC484 into clinical trials.